A review of dissolved gas analysis measurement and interpretation techniques - Abu Bakar, Norazhar (2014)
Dissolved Gas Analysis (DGA) is widely accepted as powerful tool in diagnosing power transformer health condition. Several DGA measurement techniques have been developed since 1950’s, from limited laboratory testing up to site online monitoring. Gas Chromatography (GC), Hydrogen on-line monitor and Photo-Acoustic Spectroscopy (PAS) are most popular among existing DGA techniques. Basic operating principle, advantages and disadvantages of GC, Hydrogen On-line Monitor and PAS are reviewed and discussed in this paper. Several DGA interpretation techniques such as Key Gas Method, Doernenburg, Rogers, IEC ratio methods and Duval Triangle method are also reviewed in this paper.